The Implementation of Electronic-Based Archiving to Accelerate Government Digitalization in Indonesia - Nur Soulthoni, Hannin Pradita; Itasari, Maya (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
The rapid advancements in technology have significantly influenced the way individuals interact and meet their needs, pushing for the digital transformation of government operations, particularly in archiving. Despite the introduction of electronic archiving systems in government institutions, physical archiving still prevails, leading to inefficiencies. This study utilizes a normative juridical method, focusing on secondary data analysis from library research. It examines the legal frameworks surrounding electronic-based archiving in Indonesia’s public sector and evaluates its role in the government's digital transformation. The research identifies that while electronic archiving is increasingly recognized as an essential tool for government efficiency, its implementation remains optional rather than mandatory. The legal certainty surrounding digital archiving is still underdeveloped, particularly in areas related to the legality of digital documents and the transition from manual to digital processes. This paper suggests that the current regulations need to be revised, specifically those concerning financial accountability and governance, to better support the transition to a paperless system. The findings emphasize that enhancing legal clarity and updating the regulatory framework are key to fostering the adoption of electronic archiving systems, thus accelerating the government's move toward a fully digital administration.